Does communication satisfaction influence job performance: a study on the Malaysian hotel industry / Muzalifah Monil, Musaiyadah Ahamadun, Muhammad Izwan Ikhsan, Masnih Mustapa and Nur Ilma Ambo - Monil, Muzalifah; Ahamadun, Musaiyadah; Ikhsan, Muhammad Izwan; Mustapa, Masnih; Ambo, Nur Ilma (UiTM Cawangan Johor, 2024)
Frontline employees play a pivotal role in shaping the public perception of the hotel industry, serving as a crucial standard for competing on service quality. This research aims to examine how emotional intelligence and communication satisfaction influence job performance among frontline employees, employing a causal steps approach. A structured survey, adapted from previous studies, measured job performance (18 items), emotional intelligence (21 items), and communication satisfaction (1 7 items) among 377 respondents from star-rated hotels in Malaysia. The findings highlight significant and positive correlations between emotional intelligence, communication satisfaction, and job performance. The study emphasises the potential for the hotel industry to enhance frontline employee performance through targeted training interventions based on these results. Keywords: Communication Satisfaction, Emotional Intelligence, Frontline Employees, Hotel Industry, Job Performance